El volumen celular - Herrera, Dr. Francisco (Gaceta Médica de Caracas, 2021)
Las células mantienen un volumen constante por la isosmoticidad de las soluciones a ambos lados de la membrana celular, a pesar de que el interior celular es rico en potasio y pobre en sodio, contrariamente al medio extracelular. Cells maintain a constant volume and isosmotic with the extracellular medium despite the high potassium and low sodium concentrations of the intracellular medium, in contrast with the high sodium and low potassium concentration of the external medium.